Comparative Online Sales Performance of Plantation-Based Beverages on Shopee (An Anova Approach) - Dika Muftia; Marisa Eka Prasetyawati (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2026)
The plantation subsector plays an important role in Indonesia's agribusiness economy, with coffee, tea, and cocoa representing major beverage commodities increasingly marketed through e-commerce platforms. However, empirical comparisons of their online sales performance remain limited. This study examines differences in sales performance among coffee, tea, and cocoa-based ready-to-drink (RTD) and instant beverages sold on the Shopee marketplace. A quantitative comparative approach was employed using secondary data from 180 product listings, comprising 60 products for each commodity. Sales volume was analyzed using One-Way Analysis of Variance (ANOVA) followed by Tukey HSD post hoc testing at the 5% significance level. The results indicate a statistically significant difference in average sales among the three commodities (F = 3.08; p = 0.048). Post-hoc analysis shows that the significant difference occurs only between coffee and tea, while cocoa exhibits overlapping sales performance with both. These findings suggest that digital competitiveness in agribusiness is selective rather than uniform across commodities. This study demonstrates the usefulness of variance-based statistical analysis for revealing structural differences in platform-based agribusiness markets. The findings further indicate that digital agribusiness competitiveness is increasingly shaped by demand-side factors and platform-mediated visibility, providing practical insights for producers and policymakers in designing targeted digital strategies.